Can Humic Substances Improve Soil Fertility under Salt Stress and Drought Conditions?. Issue 6 (1st November 2019) - Suddarth, Stella R. P.; Ferreira, Jorge F. S.; Cavalcante, Lourival F.; Fraga, Vânia S.; Anderson, Ray G.; Halvorson, Jonathan J.; Bezerra, Francisco T. C.; Medeiros, Sherly. A. S.; Costa, Cassio R. G.; Dias, Nildo S.
Abstract : Semiarid soils may be poor in organic carbon, a necessary source of energy for soil microorganisms that affect plant growth. Although the addition of organic carbon may improve soil chemical characteristics, the concentration of humic compounds in the organic component may vary and affect soil chemical composition. We evaluated the effect of two sources of humic compounds on a dystrophic yellow Oxisol cultivated with passion fruit ( Passiflora edulis Sims f. edulis ) and irrigated with saline water during a severe drought in the Brazilian semiarid region. Soil fertility was evaluated during two seasons. A bovine biofertilizer and an organic commercial amendment (Humistar) were used as sources of humic compounds. Salinity resulted in reduced soil fertility, mainly during the lower rainfall period. The combination of humic substances and salinity increased soil salinity. Humistar, more concentrated in humic acid than fulvic acid, increased both acidity and salinity of the Oxisol under study during the lower rainfall period. Our results contradict the general idea that organic matter can mitigate the harmful effects of salts in semiarid soils because the addition of organic sources to the soil, mainly during a severe drought period, may reduce soil fertility. Although this response may depend on the concentration of humic acids in the amendment, our results suggest that the correction of soil chemistry with the application of either amendment to Oxisols under semiarid conditions, mainly during severe drought, is not economically feasible. Core Ideas: Saline irrigation reduces the fertility of Oxisols, mainly in low‐rainfall periods. The combination of humic substances and salinity increased salinity of Oxisols. During low‐rainfall periods, humic substances reduced Oxisol fertility.